التغيرات السكانية ومشـــكلات النمو السكاني في منطقة قصر الأخيار خلال الفترة 1984 – 2020م - الحاتمي عبدالرزاق علي (مجلة الاصالة, 2024)
التغيرات السكانية ومشـــكلات النمو السكاني في منطقة قصر الأخيار خلال الفترة 1984 – 2020م